Unravelling The Bioactivities of Acmella paniculata Extract-Mediated Green Deep Eutectic Solvent of Citric Acid Monohydrate and Glycerol - Sivaraj, Rajina Shahmir; Hanaphi, Roziana Mohamed; Yusof, Rizana (Malaysian Applied Biology, 2024)
Plants are important sources of underlying medicinal value properties. The extraction of bioactive compounds from botanical sources using green solvents has gained interest due to its environmental sustainability. This study highlighted the bioactivities potential of Acmella paniculata extract mediated by green deep eutectic solvent (DES) composed of the citric acid monohydrate and glycerol. Acmella paniculata, a local flowering shrub was selected due to its rich medicinal value compounds. The synergistic effect between plant’s bioactive compounds and DES is capable of enhancing bioactivity, making DES a promising plant solvent extractor candidate. The plant extracts were prepared in leaf and flower parts using the centrifugation method. The phytochemical screening for both extracts showed the presence of terpenoids and steroid constituents which have valuable bioactivity functions. The antibacterial activity assessed by disc diffusion assay exhibited higher susceptible bacterial response of E. coli, Salmonella enterica ser. Typhimurium and S. aureus against the flower extract compared to the leaf extract. The DPPH assay was conducted to assess free radical scavenging activity. The flower extract demonstrated radical scavenging activity (RSA) of 75%-77% while the leaf extract demonstrated 65%-69%. The flower extract results showed higher RSA emphasizing its potential as a natural antioxidant. The anti-inflammatory activity was determined by egg albumin denaturation assay, which showed a greater inhibition rate in flower extract than the leaf extract which was up to 95% and 89% respectively. Thus, both extracts possess an in vitro anti-inflammatory effect. Conclusively, flower extract exhibited better bioactivities value than leaf extract in a green DES. Hence, offering a new insight into its application as an effective alternative in natural product-based therapeutics.